2014
DOI: 10.1016/j.jagp.2012.12.216
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Disorders and Pain Treatment in Community Nursing Homes

Abstract: Objectives Effective pain assessment and pain treatment are key goals in community nursing homes, but residents’ psychiatric disorders may interfere with attaining these goals. This study addressed whether: (a) pain assessment and treatment obtained by nursing home residents with psychiatric disorders differs from that obtained by residents without psychiatric disorders; (b) this difference is found consistently across the four types of psychiatric disorder most prevalent in nursing homes (dementia, depression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Our estimate of the prevalence of depression upon nursing home admission is consistent with the previous estimates (Bagchi et al ., ; Brennan & SooHoo, ). Given the Centers for Medicare and Medicaid Services quality indicator highlighting the importance of recognizing depression in the nursing home setting, we were somewhat surprised that less than half received any form of treatment for their depression.…”
Section: Discussionmentioning
confidence: 99%
“…Our estimate of the prevalence of depression upon nursing home admission is consistent with the previous estimates (Bagchi et al ., ; Brennan & SooHoo, ). Given the Centers for Medicare and Medicaid Services quality indicator highlighting the importance of recognizing depression in the nursing home setting, we were somewhat surprised that less than half received any form of treatment for their depression.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, residents with psychiatric disorders, and especially those suffering from dementia, are less likely than residents without psychiatric disorders to be rated as having pain. [ 25 ] Nursing home staff are still experiencing problems identifying signs of psychiatric disorder. [ 26 ] Previous research among Spanish elderly institutionalized in residential care facilities has shown that over a period of 20 months, there was a significant decrease in resident QoL.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the most recent version of the Centers for Medicare and Medicaid Services (CMS) Nursing Home Data Compendium (CMS, 2016), just over 1.4 million residents were residing in U.S. nursing homes on December 31, 2014, corresponding to 2.6% of the over-65 population and 9.5% of the over-85 population. It has been found that among long-term care residents, approximately 75% of residents have one or more mental health diagnosis (Brennan & SooHoo, 2020), with dementia, depression, anxiety disorders, and serious mental illness being the most prevalent (Brennan & SooHoo, 2014, 2020; Lemke & Schaefer, 2010). Although there is strong overlap between the skills of psychologists working in long-term care (LTC) and those working in other settings, there are unique aspects of the provision of care in LTC settings.…”
Section: Provision Of Services In Specific Settingsmentioning
confidence: 99%